Hak Ulayat Masyarakat Hukum Adat Dalam Implementasi Pembangunan Hukum Nasional di Indonesia - Rodhiyah Mardhiya (CV Rewang Rencang, 2024)
This article discusses the legal politics of customary rights (land, rivers and wild animals) by customary law communities in the implementation of national legal development in Indonesia. This study aims to explain the existence of community customary rights, the existence of indigenous peoples' customary rights in the development of national law and about the resolution of problems related to customary rights within the scope of national legal regulation. This research is a category of qualitative research using a method, namely descriptive analysis, namely a method of finding facts, in this case using data sources, books, journals, laws, guidelines for solving customary rights problems in the UUPA and other literature precisely and straightforwardly, the type of data used is in the form ofofficial documents and scientific literature with literature study data collection techniques, then this research uses a normative juridical approach by including theories, principles, and applicable laws and regulations. The results show that the customary rights of customary law communities are still recorded in existence as long as the customary law of an indigenous community is still trusted and carried out in daily life so that it becomes a tipping point for consideration in the development of national law and the resolution of problems related to customary rights law of customary law communities accommodated in various regulations from laws, regional regulations, circulars, as well as other legal rules.